Induced Pluripotent Stem (iPS) Cells Methods and Protocols - Turksen, Kursad; Nagy, Andras; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana Press, 2016)
This volume aims to be a collection of essential protocols in iPS cell field. Induced Pluripotent Stem (iPS) Cells: Methods and Protocols guides readers through multiple facets of stem cell biology, lineage commitment and differentiation. Written for the Methods in Molecular Biology series, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and practical, Induced Pluripotent Stem (iPS) Cells: Methods and Protocols provides protocols that can be used by both experts and novices interested in stem cells. .
The piggyBac Transposon as a Platform Technology for Somatic Cell Reprogramming Studies in Mouse -- Vallier Generation of Human Induced Pluripotent Stem Cells from Peripheral Blood Mononuclear Cells Using Sendai Virus -- Virus-based Reprograming of Mesenchymal Stromal/Stem Cells from Umbilical Cord Wharton$1 (Bs Jelly into Induced Pluripotent Stem Cells -- Very Rapid and Efficient Generation of Induced Pluripotent Stem Cells from Mouse pre-B Cells -- Generation of iPS cells from Human Peripheral Blood Mononuclear Cells Using Episomal Vectors -- Enhancing Induced Pluripotent Stem Cell Generation by MicroRNA -- Generation of Partially Reprogrammed Cells and Fully Reprogrammed iPS Cells By Plasmid Transfection -- Using Oct4:MerCreMer Lineage Tracing to Monitor Endogenous Oct4 Expression During the Reprogramming of Fibroblasts to Induced Pluripotent Stem Cells (iPSCs) -- Inducible Transgene Expression in Human iPS Cells Using Versatile All-in-One piggyBac Transposons -- Generation and Characterization of Rat iPSCs -- Generation of Induced Pluripotent Stem Cells in Rabbits -- Monkey Induced Pluripotent Stem Cells Generated by Using Allogeneic Genes -- Induced Pluripotent Stem Cells from Nonhuman Primates -- Computational Biology Methods for Characterization of Pluripotent Cells -- cGMP-compliant Expansion of Human iPSC Cultures as Adherent Monolayers -- Analysis of the Mitochondrial DNA and its Replicative Capacity in Induced Pluripotent Stem Cells -- Selection of Phage Display Peptides Targeting Human Pluripotent Stem Cell Derived Progenitor Cell Lines -- piggyBac Transposon Mediated Reprogramming and Flow Cytometry Analysis of CD44 and ICAM1 Cell-Surface Marker Changes -- Generation and in vitro Expansion of Hepatic Progenitor Cells from Human iPS Cells -- Induced Pluripotent Stem (iPS) Cell Culture Methods and Induction of Differentiation into Endothelial Cells -- Derivation of Neural Stem Cells from Mouse Induced Pluripotent Stem Cells. Production of Retinal Cells from Confluent Human iPS Cells -- Differentiation of iPSC to Mesenchymal Stem-Like Cells and their Characterization -- Hepatic Differentiation from Human iPS Cells using M15 Cells -- Determination of Functional Activity of Human iPSC-derived Hepatocytes by Measurement of CYP Metabolism -- Mesoderm Differentiation from hiPS Cells -- Enhancing Human Cardiomyocyte Differentiation from Induced Pluripotent Stem Cells with Trichostatin-A -- Derivation of Skeletal Myogenic Precursors from Human Pluripotent Stem Cells Using Conditional Expression of PAX7 -- Chondrogenic and Osteogenic Induction from iPS Cells -- Generation of iPS Cells from Granulosa Cells -- The Characteristics of Murine iPS Cells and siRNA Transfection under Hypoxia -- Hepatic Differentiation from Murine and Human iPS cells using Nanofiber Scaffolds.s
Keywords: Life sciences; Cell biology; Life Sciences; Cell Biology; Electronic books